Managing pension funds: issues for reform - Kannan, R. (2004)
Three issues - the absence of mortality table for the annuitants, lack of reinsurance arrangements and who is best suited to manage the funds during the accumulation phase - deserve urgent attention in the context of the government's new initiatives on pension reform. - Reproduced.
Keywords: Pensions